Logic demystified - Boutelle, Anthony. 4 0 16; Gibilisco, Stan; 5 (New York : McGraw-Hill, 2011)
Offers easy-to-understand coverage of this intriguing topic, which spans mathematics, engineering, science, philosophy, debate, political science, and law. This accessible guide contains numerous self-test questions with answer keys, in addition to problems posed and solved in the course of the text.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Logic -- 20 -- Textbooks; 20; 2